Physician Survey Results: Clinical Practice Training Is Needed to Improve Ob/Gyn PrEP Adoption [02A]. (May 2020) - Simoncini, Gina M.; Koren, David E.; D'Avanzo, Paul A.; Diaz Quinones, Juan J.; Brajuha, Jesse; Bass, Sarah B.
Abstract : INTRODUCTION: Human immunodeficiency (HIV) disease prevention with pre-exposure prophylaxis (PrEP) is marred by disparities, especially among women and other high risk groups. PrEP prescribing adoption by primary care physicians including obstetrics and gynecology (Ob/Gyn) providers is crucial to improve HIV prevention. METHODS: We modified a previously validated PrEP provider survey and administered it online through REDCap to faculty and categorical residents in the Departments of Ob/Gyn and General Internal Medicine (GIM) of a large urban hospital. T-tests and chi-square tests were performed with an alpha significance value of 0.05. RESULTS: 61 provider-surveys were completed (24 Ob/Gyn, 37 GIM). No statistically significant differences were observed by age or race, however there were a higher proportion of female-identified providers in Ob/Gyn (87.5%) compared to GIM (54.1%) ( P =.01). The Ob/Gyn surveys demonstrated significant differences in the clinical processes for PrEP management. Surveys demonstrated perceived deficiencies in provider training/education ( P =.006), clinical practice guidelines ( P =.001), availability of resource access (such as PrEP guidelines/protocols) ( P =.003), peers/colleagues who are knowledgeable about or supportive of PrEP provision within their practice ( P =.008), and lab monitoring requirements ( P=. 019). GIM respondents were more likely to believe they knew enough about PrEP to feel comfortable prescribing it ( P =.005), thought it was feasible to prescribe in GIM and OB/Gyn settings compared to HIV prevention/care clinics ( P =.019) and to say they would be likely to prescribe PrEP in the next 6 months ( P =.01). CONCLUSION: Overall, results indicate that improved clinical practice training and processes are necessary to increase PrEP adoption in OB/Gyn clinical settings.